Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1103/physrevb.80.104518
|View full text |Cite
|
Sign up to set email alerts
|

Universal critical behavior in single crystals and films ofYBa2Cu3O7δ

Abstract: We have studied the normal-to-superconducting phase transition in optimally doped YBa 2 Cu 3 O 7−␦ in zero external magnetic field using a variety of different samples and techniques. Using dc transport measurements, we find that the dynamical critical exponent z = 1.54Ϯ 0.14, and the static critical exponent = 0.66Ϯ 0.10 for both films ͑when finite-thickness effects are included in the data analysis͒ and single crystals ͑where finitethickness effects are unimportant͒. We also measured thin films at different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…9,10 Recently, it has been shown that the original experimental results in thin films can be analyzed properly only by accounting for the finite size effects and the value of z then extracted. 86 In microwave measurements, the phase of the complex fluctuation conductivity at T c is often taken as a sensitive probe for the value of z. However, the extracted value of z may still be incorrect if the effect of the short wavelength 144508-8 cutoff at T c is not accounted for properly.…”
Section: Analysis Of the Complex Conductivity Due To Superconductimentioning
confidence: 99%
“…9,10 Recently, it has been shown that the original experimental results in thin films can be analyzed properly only by accounting for the finite size effects and the value of z then extracted. 86 In microwave measurements, the phase of the complex fluctuation conductivity at T c is often taken as a sensitive probe for the value of z. However, the extracted value of z may still be incorrect if the effect of the short wavelength 144508-8 cutoff at T c is not accounted for properly.…”
Section: Analysis Of the Complex Conductivity Due To Superconductimentioning
confidence: 99%
“…Most notably, we have shown that the finite thickness of the films, even of "thick" films ͑d Ն 3000 Å͒, obscures the phase transition. 14 We have found that when we account for these effects, the phase transition in hole-doped YBa 2 Cu 3 O 7−␦ ͑YBCO͒ films and crystals yields consistent exponents for both dc and microwave conductivity measurements, = 0.68Ϯ 0.07, as predicted by three-dimensional ͑3D͒ XY theory; and z = 1.5Ϯ 0.2, 15 indicating Model E dynamics. 16 In this paper we report on the zero-field normalsuperconducting phase transition of the electron-doped su-perconductors and present data on the critical regime of Pr 2−x Ce x CuO 4−y ͑PCCO͒ thin films ͑ranging in thickness from d Ϸ 2000 Å to d Ϸ 3000 Å͒ for a variety of different cerium dopings ͑x͒.…”
Section: Introductionmentioning
confidence: 67%
“…Our data confirm this hypothesis: at the smallest transition widths, we find z Ϸ 1.5 in optimally doped and x = 0.16 films, similar to results in YBCO. 15 However, as the transition width increases the dynamic critical exponent tends toward z = 1. Our results imply that only in more homogenous films with transition widths smaller than current transition widths will we be able to unambiguously see critical dynamics for all dopings ͑though whether all dopings will have the same dynamic critical exponent as optimally doped PCCO and YBCO is unknown͒.…”
Section: Dynamic Critical Exponentmentioning
confidence: 99%
See 2 more Smart Citations